Quadro editorial (Estudos em Design, 2022)
EditoresCristina PortugalRita Maria de Souza Couto Avaliadores desta edição v. 30, n. 3 (2022) Alexandre Farbiarz Alexandre Oliveira Aline Savi Álvaro Sousa Ana Berwanger André Ribeiro de Oliveira Andréa Almeida Andréa Silva Adriana Miranda Adriana Sampaio Leite Antonio Colchete Beany Monteiro Cayley Guimaraes Claudio Ferreira Clice Mazzilli Cristiane Aun Bertoldi Cyntia Malaguti de Sousa Daniel Lacerda Rodrigues Edson Rufino Eva Rolim Miranda Gabriela Carneiro Gabriel Patrocinio Helena Barbosa Jade Piaia Joana Contino Kando Fukushima Kátia Carvalhaes Pêgo Karen Bosy Klaus Alberto Laura Martins Letícia Fonseca Linda Linn Livia Flavia Campos Luiz Antonio de Saboya Luiza Falcão Soares Cunha Matheus Cezarotto Marcelo Bezerra Marcio Guimarães Marcos Braga Marina Kunst Mariano Lopes de Andrade Neto Maristela Ono Nelson Kuwahara Olavo Neto Paula Piva Linke Rafaella Peres Ranielder de Freitas Renata Wanderley Sandra Maria Souza Sérgio Luciano da Silva Tiago Silva Vagner Godói Vera Damazio Verônica Freire Viviane Nunes